A revision of the genus Neosclerus Cameron. Supplement I (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2011)
Neosclerus immutatus sp. n. (Sumatra) is described and illustrated. A recent key to the species of the genus is modified in order to account for the new species. Additional paratypes are listed for N. dupleseriatus sp. n. (N. India, central Nepal) and N. praeacutus sp. n. (Thailand). Additional records of N. fortepunctatus Cameron, 1924 (first confirmed record) and N. granulicollis Cameron, 1924 (new country record) from Nepal are reported. The genus now includes 27 species.KeywordsColeoptera, Staphylinidae, Paederinae, Medonina, Neosclerus, Palaearctic region, Oriental region, taxonomy, new species, key to species, additional records.Nomenclatural Actsdupleseriatus Assing, 2011 (Neosclerus), spec. nov. (additional paratypes, original description see Assing, 2011, p. 96)immutatus Assing, 2011 (Neosclerus), spec. nov.praeacutus Assing, 2011 (Neosclerus), spec. nov. (additional paratypes, original description see Assing, 2011, p. 105)